Investigation of firebrand generation from an experimental fire: Development of a reliable data collection methodology. (July 2017) - Thomas, Jan C.; Mueller, Eric V.; Santamaria, Simon; Gallagher, Michael; El Houssami, Mohamad; Filkov, Alexander; Clark, Kenneth; Skowronski, Nicholas; Hadden, Rory M.; Mell, William; Simeoni, Albert
Abstract: An experimental approach has been developed to quantify the characteristics and flux of firebrands during a management-scale wildfire in a pine-dominated ecosystem. By characterizing the local fire behavior and measuring the temporal and spatial variation in firebrand collection, the flux of firebrands has been related to the fire behavior for the first time. This linkage is seen as the first step in risk mitigation at the wildland urban interface (WUI). Data analyses allowed the evaluation of firebrand flux with respect to observed fire intensities for this ecosystem. Typical firebrand fluxes of 0.82–1.36 pcs m −2  s −1 were observed for fire intensities ranging between 7.35±3.48 MW m −1 to 12.59±5.87 MW m −1 . The experimental approach is shown to provide consistent experimental data, with small variations within the firebrand collection area. Particle size distributions show that small particles of area 0.75–5×10 −5  m 2 are the most abundant (0.6–1 pcs m −2  s −1 ), with the total flux of particles >5×10 −5  m 2 equal to 0.2–0.3 pcs m −2  s −1 . The experimental method and the data gathered show substantial promise for future investigation and quantification of firebrand generation and consequently a better description of the firebrand risk at the WUI.